Luteolin Inhibits Vascular Smooth Muscle Cell Proliferation and Migration by Inhibiting TGFBR1 Signaling - Wu, Yu-Ting; Chen, Ling; Tan, Zhang-Bin; Fan, Hui-Jie; Xie, Ling-Peng; Zhang, Wen-Tong; Chen, Hong-Mei; Li, Jun; Liu, Bin; Zhou, Ying-Chun (Frontiers in Pharmacology, 2018)
Vascular smooth muscle cell (VSMC) proliferation and migration play a critical role in the development of arterial remodeling during various vascular diseases including atherosclerosis, hypertension, and related diseases. Luteolin is a food-derived flavonoid that exerts protective effects on cardiovascular diseases. Here, we investigated the effects and mechanism of luteolin on VSMC proliferation and migration. We found that this compound reduced the proliferation and migration of VSMCs, specifically A7r5 and HASMC, in a dose-dependent manner, based on MTS, EdU, Transwell, and wound healing assays. We also demonstrated that it inhibited the expression of proliferation-related proteins including PCNA and Cyclin D1, as well as the migration-related proteins MMP2 and MMP9, in a dose-dependent manner by western blotting. In addition, luteolin dose-dependently inhibited the phosphorylation of transforming growth factor-β receptor 1 (TGFBR1), Smad2, and Smad3. Notably, adenovirus-mediated overexpression of TGFBR1 enhanced TGFBR1, Smad2, and Smad3 activation in VSMCs and partially blocked the inhibitory effect of luteolin on TGFBR1, Smad2, and Smad3. Moreover, overexpression of TGFBR1 rescued the inhibitory effects of luteolin on the proliferation and migration of VSMCs. Additionally, molecular docking showed that this compound could dock onto an agonist binding site of TGFBR1, and that the binding energy between luteolin and TGFBR1 was −10.194 kcal/mol. Simulations of molecular dynamics showed that TGFBR1-luteolin binding was stable. Collectively, these data demonstrated that luteolin might inhibit VSMC proliferation and migration by suppressing TGFBR1 signaling.